4th International Symposium on Voronoi Diagrams in Science and Engineering (ISVD 2007) 2007
DOI: 10.1109/isvd.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

Voronoi Tessellations and the Cosmic Web: Spatial Patterns and Clustering across the Universe

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…While other cosmic structure analysis tools do not include a facility to select weblike features according to tailor-made aspects and characteristics, this is precisely the mission of the Felix procedure. We directed Felix towards a case study of the the filamentary infrastructure and architecture of cosmic voids and demonstrated that it successfully extracts the network of tenuous filaments pervading their interior [72], [73], [74], [75] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While other cosmic structure analysis tools do not include a facility to select weblike features according to tailor-made aspects and characteristics, this is precisely the mission of the Felix procedure. We directed Felix towards a case study of the the filamentary infrastructure and architecture of cosmic voids and demonstrated that it successfully extracts the network of tenuous filaments pervading their interior [72], [73], [74], [75] .…”
Section: Resultsmentioning
confidence: 99%
“…They use Voronoi tessellations as a template for distribution of matter and related galaxy population [76], [77], [74], and its subsequent evolution.…”
Section: Voronoi Evolution Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voronoi Clustering Models are a class of heuristic models for cellular distributions of matter which use the Voronoi tessellation as the skeleton of the cosmic matter distribution [30], [31], [32].…”
Section: Voronoi Clustering Modelsmentioning
confidence: 99%
“…This concerns not only the values and range over which β 2 reaches a maximum, as for the pure filament and wall models, but even entirely different systematic behaviour in the case of the more elaborate and complex Voronoi kinematic models (see e.g. the review by Van de Weygaert 2010 [34] and [32]). …”
Section: Number Of Holes: βmentioning
confidence: 99%